The hybrid concept in lip reconstruction - Abdulrauf, Badr M. I. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Local tissues are best suited for lip reconstruction. The defect following cancer resection is often significant where standard methods are often suboptimal. Here we are presenting 3 such cases. Case 1, a 65 years old male post squamous cell carcinoma (SCC) resection with 50% defect of lower lip and a commissure, reconstructed with Estlander flap and a unilateral Karapandzik flap on opposite side. Case 2, a 35 years old male had a similar kind of defect, reconstructed with Estlander flap and step-plasty on opposite side. Case 3, a 70 years old female with 80% central lower lip defect post SCC resection, was reconstructed with bilateral Karapandzik flaps and an Abbe flap. Considering the significant size defect, all cases healed quite satisfactorily. They maintained their oral competence with negligent microstomia. The hybrid principle of combining various reconstructive techniques is highly recommended for major lip defects.